Selective deficits of S-cone in thyroid-associated ophthalmopathy patients without clinical signs of dysthyroid optic neuropathy - Jin, Haochen; Yu, Xi; Cao, Suqi; Wang, Mengting; Hu, Xiaozhou; Ye, Jie; Liu, Weijie; Xu, Mingna; Wu, Wencan; Tu, Yunhai (Frontiers in Neuroscience, 2022)
Purpose: We explored whether thyroid-associated ophthalmopathy (TAO) patients without clinical signs of dysthyroid optic neuropathy (DON) would have a selective deficit mediated by S-cone. Methods: Thirty-two TAO patients without clinical signs of DON (non-DON, 42.03 ± 9.59 years old) and 27 healthy controls (41.46 ± 6.72 years old) participated in this prospective, cross-sectional study. All observers were tested psychophysically after passing color screening tests and a comprehensive ocular examination. Isolated L-, M-, and S-cone contrast thresholds were measured at 0.5 cyc/deg using Gabor patches. We calculated the area under the receiver operating characteristic curve to quantify the ability of chromatic contrast sensitivity to detect the early visual function changes in non-DON patients. Results: S-cone contrast sensitivity in non-DON patients was found to be lower than that of healthy controls (P < 0.001), whereas the sensitivities to L- and M-cone Gabor patches were similar between these two groups (P = 0.297, 0.666, respectively). Our analysis of the receiver operating characteristic curve revealed that the sensitivity to S-cone had the highest index to discriminate non-DON patients from healthy controls (AUC = 0.846, P < 0.001). The deficit of S-cone was significantly correlated with muscle index in non-DON patients (R = 0.576, P = 0.001). Conclusion: There is a selective S-cone deficit in the early stage of TAO. S-cone contrast sensitivity could serve as a sensitive measure of visual impairments associated with early DON in patients with TAO.